Development of Novel Formulation Strategies to Improve Pharmacokinetic Profile of Resveratrol - Basavaraj (Curtin University, 2011)
Resveratrol is a natural occurring polyphenol with diverse biological activities in vitro and poor pharmacokinetic profile because of its rapid metabolism in vivo. In this project, polymer conjugate approach was evaluated for masking resveratrol against the metabolism. Various polymer conjugates were prepared and evaluated both in vitro and in vivo. Among those tested, resveratrol-PLA-PEG and resveratrol-PEG ether conjugates were found capable of providing better pharmacokinetics than native resveratrol.